IMPROVING WORKING AGE YOUTH ENTREPRENEURS SKILLS WITH PRODUCT QUALITY IMPROVEMENT TRAINING AND CUPPING COFFEE TESTS TO FACE NEW NORMAL CHALLENGES IN NORTH ACEH - Zahara, Hafni; Fadli, Fadli; Tambarta, Emmia; Sinta, Irada (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2022)
The increasingly massive Corona Virus Disease (COVID-19) pandemic has recently changed the system/order of people's lives in Indonesia. This system is known as the New Normal Era. At this time, the existing employment system in Indonesia forced various job providers to reduce the number of workers due to capital problems and social distancing rules. The prohibition of gathering in one place en masse caused job providers to lay off some employees, thus increasing the number of unemployed. This also happened in North Aceh District. Many young workers are forced to leave work because of the limited job opportunities available in North Aceh District. The formation of a new business/business accompanied by the skill of understanding the quality of the product to be produced is the best solution in this condition. Understanding product quality will certainly help entrepreneurs to determine market segmentation, marketing strategies, production costs, types of raw materials used and what risks must be faced. One of the businesses that are very popular with entrepreneurs today is the business of processed drinks from Arabica coffee commodities. Arabica coffee from Aceh Province is better known as Gayo coffee. Gayo coffee is quite famous in the world because it has a distinctive aroma and enjoyment and if it is cupped or taste tested. The location of community service is taken in the North Aceh Regency area considering the location of the Faculty of Agriculture, Malikussaleh University which is located in North Aceh Regency, it is expected to be able to make a direct contribution to reducing unemployment through deepening entrepreneurial skills in working age youth through product quality improvement training and coffee test cupping to face new normal challenge in north aceh. The implementation method is designed for mentoring in the form of a participatory approach and refers to the adult learning process (adult-learning) which consists of: (1) Presentation of material equipped with Power Point presentations and simulation materials, (2) limited discussion in accordance with health protocols to prevent the spread of COVID, (3) the assignment or practice of physical testing and coffee cupping tests are (1) to produce agents of change in the "job creation" paradigm from the "job seeker" paradigm among working-age youth, (2) become a forum for soft skills training related to product quality for youth of working age as a provision for business/business formation activities, (3) as a reference for the next community service activity. The output targets to be achieved from this activity are:Publication of activities in print or online media, (3) Survey/Questionnaire of Understanding Product Quality Control to assess the improvement of Human Resources competitiveness.